Penerapan KMARI Nomor 702 Tahun 2016 Sebagai Upaya Nyata Menuju Kualitas Penjaminan Mutu Perguruan Tinggi Pada Kementerian Agama - Subagiasta, I Ketut (LPM IHDN Denpasar, 2017)
This article entitled â€œThe Application of KMARI No. 702 year of 2016 as a Real Effort toreach the Quality Assurance of High Institution in Religion Ministryâ€. Some descriptions of this article cover introduction such as basis law engagement performance, report engagement, and review on report performance, some components in KMARI Nomor 702 year of 2016, understanding performance engagement, understanding of engagement performance, and meaning review on report of performance. Then also described about purpose arranging angagement performance, arranging angagement performance, purpose report performance, form, delivery, report performance yearly, performance yearly, measuring performance, indidcator performance, and indicator main of performance, purpose review on report performance, arrangement review on report performance. Last of this article namely about conclusion and reflection.